2021
DOI: 10.1039/d1lc00518a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and improving FDM 3D printing to fabricate high-resolution and optically transparent microfluidic devices

Abstract: The fabrication of microfluidic devices through Fused Deposition Modeling (FDM) 3D printing has faced several challenges, mainly regarding obtaining microchannels with suitable transparency and sizes. Thus, the use of this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 46 publications
0
43
0
2
Order By: Relevance
“…As already mentioned, the minimum print resolution depends on many different parameters (design, capabilities of the printer, print material). For example, the structure size is <0.1 mm and the layer height of <0.1 mm and wall thicknesses of <0.1 mm [ 90 ].…”
Section: Methods For Manufacturing Microfluidic Structures For Biosen...mentioning
confidence: 99%
“…As already mentioned, the minimum print resolution depends on many different parameters (design, capabilities of the printer, print material). For example, the structure size is <0.1 mm and the layer height of <0.1 mm and wall thicknesses of <0.1 mm [ 90 ].…”
Section: Methods For Manufacturing Microfluidic Structures For Biosen...mentioning
confidence: 99%
“…34 The low transparency was likely caused by the high roughness of 3D printed surfaces characterized by large empty spaces between the junctions of the printed layers. 59 Therefore, improving the smoothness of the 3D-printed surfaces might help in enhancing the optical transparency of the devices. Although post-printing methods, such as the treatment of the 3D printed surfaces with organic solvents, have been used to improve the smoothness of the surfaces, this might compromise the resolution if micrometric internal structures are required.…”
Section: Critical Reviewmentioning
confidence: 99%
“…Although post-printing methods, such as the treatment of the 3D printed surfaces with organic solvents, have been used to improve the smoothness of the surfaces, this might compromise the resolution if micrometric internal structures are required. 59 To understand the causes of the low transparency and high roughness in most FDM-based microuidic devices and potentially resolve those issues, Quero et al conducted a theoretical and experimental study. 59 They found that the dimensions of the printer nozzle play a major role in the thermal radiation effects that limit the 3D printing resolution (Fig.…”
Section: Critical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one of the main ways to modify FDM printers is through their nozzles because they are the final part in contact with the filament before it is extruded. [ 65 ] Figure 5 A shows a modified FDM printing process to build a colorimetric enzyme‐linked immunosorbent assay (ELISA) to detect malaria. [ 66 ] Different print settings including layer height, extrusion speed as well as extrusion temperature were changed to improve bonding between layers.…”
Section: Manufacturing Principles and Approachesmentioning
confidence: 99%